To Improve Employee Career Success through Organizational Development Intervention: An Action Research of AIA Co., LTD. Changzhou Branch - Lin, Dong; Kim, Seongdok (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
This study was aimed at the research of the organization development interventions on the employee career competency, emotional intelligence and self-efficacy to improve the employee career success in AIA Changzhou Branch, China. These three variables were regarded as employee career success behaviours and closely related to the development of the focal organization in current study. Both quantitative and qualitative methods were utilized. The research methods were the questionnaire, semi-structured interview and participatory observation. Quantitative data was collected to examine the change in level of career competency, emotional intelligence and self-efficacy and qualitative data was collected to obtain in-deep understanding on the result of organization development interventions on the employees. The paired sample t-test was utilized in this study as a statistical tool to prove hypotheses. The collected data confirmed that there was an improvement of the career competency, emotional intelligence and self-efficacy after the organization development interventions. The research findings supported the research objectives and approved the hypotheses. This research responded to the organization’s needs of sustained developing and solved the company's existing problems. The results ODI of this research could be the useful tool to manage young employees and was adapted to the unpredictable and uncertain business environment. Meanwhile, the researcher designed an improvement framework to help individuals improve their career competency, emotional intelligence and self-efficacy and to achieve career success and better career development in an uncertain borderless career period.